RETRACTED: Experiments on pressing elastic-viscous products - Bahadirov Gayrat; Nabiev Ayder; Tsoy Gerasim (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001